Pengaruh Persepsi Auditor atas Integritas terhadap Kualitas Audit pada Kantor Akuntan Publik di Kota Makassar - Eva Marin Sambo; Sumiati Sumiati (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2021)
This study aimed to determinethe effect on the auditor’s perception of the quality audit integrity in thepublic accounting firminthe city of Makassar. The population in this study were all auditors working at the firm in the city of Makassar. Sampling techniques Sampling method nonprobability (saturated sample) in order to obtain a sample of 34 respondents. Data analysis method used in this research is simple regression analysis.These results indicatethat the perception integrity of the integrity of the auditorson thebasisof partialpositive and significant impacton audit quality. The contribution rateinfluencesthe integrityof theauditors onauditqualityis high.This is caused bysome ofthe respondentsansweredpositivelyvariableneutralstatementof integrityandquality of theaudit.